Approaches to Proximal Tibial Bone Harvest Techniques - Brion Benninger, `; Brion Benninger; Taylor Delamarter (Stilus Optimus, 2012)
Objectives: The iliac crest is the standard site for harvesting bone; however, this procedure may require another specialist and a general anaesthetic. The proximal tibial bone harvest has gained popularity for harvesting autogenous bone. An analysis of the clinical literature regarding the various regions for harvesting bone demonstrates that the use of the proximal tibia led to shorter hospital stays, lower morbidity rates, and a shorter learning curve for the surgeon. The purpose of this study was to analyze the clinical anatomy of a proximal tibial bone harvest graft to provide the anatomical architecture supporting a safe procedure.Materials and Methods: Dissection of 58 lower limbs from embalmed cadavers was conducted to determine the anatomy of a proximal tibial bone harvest (PTBH). Results: Dissection revealed that the medial approach has fewer clinically relevant neurovascular structures in harms way, and a larger surface area, providing the clinician a confident surgical window to perform the procedure.Conclusions: The anatomical basis of this study suggests that the medial proximal tibial bone harvest approach would have fewer serious structures in harm's way compared to the lateral; however, the lateral approach may be preferred for a subgroup of patients.